Effectiveness of drug postmarketing all-case surveillance as a safety measure in Japan. (December 2021) - Kondo, Hideyuki; Masamune, Ken
Introduction: The drug pharmacovigilance system in Japan is similar to those in the European Union (EU) and the United States. As a unique Japanese pharmacovigilance program, postmarketing all-case surveillance (PMACS) is required. PMACS plays a key role for postmarketing activities, but there are challenges that place much burden on PMACS conduct. This study investigates the impact of PMACS on postmarketing activities in Japan and proposes its potential improvement. This study also seeks the possibility to expand PMACS beyond Japan. Materials and Methods: Reexamination reports issued from 2017 to 2019 were identified in September 2020 by searching 'reexamination report' and '201701' to '201912' on the Pharmaceuticals and Medical Devices Agency website. The corresponding Package Insert (PI) change orders and premarketing review reports were also identified. Reviewing these regulatory documents allowed for investigation of the PMACS impact on postmarketing activities. Results: More than half (57%) of the drugs with PMACS had 'Limited dosing experience in Japan' as a reason for the PMACS requirement. As a safety measure, no PI change orders were imposed on 33% and 28% of drugs with and without PMACS, respectively. The means of the number of PI change orders were 2.23 and 2.14 for drugs with and without PMACS, respectively. There were no reexamination reports mentioning any concerns related to efficacy. Discussion and Conclusion: PMACS should not be imposed only because of limited dosing experience in Japan at the premarketing stage. Rather, PMACS should focus on (1) collection of safety data (not efficacy), (2) necessity of distribution control, and/or (3) collection of case details for drugs with a limited treated population. PMACS also has the potential to be utilized in the EU and the United States, as their regulatory frameworks are acceptable for PMACS. Naglazyme (galsulfase) is a case where the PMACS-like studies have been required in each region. Plain Language Summary: Effectiveness of data collection for all patients who receive a new drug as a safety measure in Japan: Introduction: In Japan, a drug company is obligated to conduct data collection after a new drug launch as an approval condition. The obligation is a unique Japanese requirement where a company must collect data from all patients receiving the drug in Japan in cooperation with hospitals. This is expected to contribute to intensive data collection and better drug distribution control and could potentially be useful in countries beyond Japan. However, no clear criteria have been established for decision making, despite the significant burden for companies and hospitals. Therefore, this study aimed to investigate the impact of the obligation on safety measures and efficacy data collection and propose a potentially improved drug scope to impose the obligation. Materials and Methods: Reexamination of reports issued by the Pharmaceuticals and Medical Devices Agency between 2017–2019. Results: More than half (57%) of the included drugs had 'Limited dosing experience in Japan' as a reason for the obligation being required. However, regulatory order to change drug label, an action based on safety signal identification, was imposed on 33% and 28% of drugs with and without the obligation, respectively. The means of the number of the label change orders were 2.23 and 2.14 for drugs with and without obligation, respectively. Meanwhile, some drugs were highlighted as potential factors for better application of the obligation. Conclusion: According to these results, the obligation should be imposed on a limited number of drugs by focusing not on dosing experience in Japan but on safety (not efficacy) data collection, necessity of distribution control, and/or collection of case details for drugs with a limited treated population. The obligation also has the potential to be utilized in the EU and the United States, as their regulatory frameworks are acceptable for the obligation.